WOMEN-WRITERS IN ENGLISH LITERATURE - Eshniyozova Jasmina Jo’rabekovna (Лучшие интеллектуальные исследования, 2024)
Annotation: A comprehensive overview of the significant social and political changes experienced by women during the Victorian era, highlighting the pivotal role of writing in advocating for women's rights and challenging traditional gender norms. It discusses how women writers utilized literature to address issues such as limited career opportunities, educational barriers, and political disenfranchisement, ultimately contributing to the emergence of feminism and the redefinition of gender roles. The concept of the "New Woman" and its impact on societal reforms, as well as the works of prominent female authors like Charlotte Bronte and their portrayal of strong female characters. Additionally, it touches upon the challenges faced by female writers in a male-dominated literary landscape and the public demand for novels that depicted themes of independence and female sexuality.